2011
DOI: 10.1159/000324205
|View full text |Cite
|
Sign up to set email alerts
|

MMP20 Cleaves E-Cadherin and Influences Ameloblast Development

Abstract: Dental enamel development occurs in stages as observed by the changing morphology of the ameloblasts that are responsible for enamel formation. During the secretory stage of development, proteins including MMP20 are secreted into the enamel matrix. MMP20 is required for proper enamel formation as mutation of the Mmp20 gene causes autosomal recessive amelogenesis imperfecta. Here, we examined in detail the morphology of the Mmp20-null ameloblast cell layer. Intriguingly, we found that the Mmp20-null mouse secre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 54 publications
(25 reference statements)
1
37
0
Order By: Relevance
“…RUNX2 is a key regulatory transcription factor that suppresses genes that are expressed during the secretory stage, such as AMGN and ENAM, and thus regulates enamel formation (28). MMP20 and KLK4 are proteases that break down enamel proteins to form a mineralized layer of enamel (23). Among the genes investigated in this study, they were the most profoundly affected genes when SDC4 expression was inhibited.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…RUNX2 is a key regulatory transcription factor that suppresses genes that are expressed during the secretory stage, such as AMGN and ENAM, and thus regulates enamel formation (28). MMP20 and KLK4 are proteases that break down enamel proteins to form a mineralized layer of enamel (23). Among the genes investigated in this study, they were the most profoundly affected genes when SDC4 expression was inhibited.…”
Section: Discussionmentioning
confidence: 89%
“…In this study, the anti-SDC4 antibody was the synthetic peptide surrounding the intracellular domain of SDC4 (22). Due to the fact that the cytoplasmic domains of the core protein are conserved, and the extracellular domain of SDC4 can be proteolytically cleaved, a process mediated by a variety of proteases of the MMP family, it can thus be suggested that the SDC4 ectodomain may be cleaved to the ameloblasts that synthesize MMP20 at the secretory stage (23).…”
Section: Discussionmentioning
confidence: 99%
“…Enamelysin (Mmp20), a matrix metalloproteinase, and the enamel serine protease kallikrein 4 (Klk4) are two major molecules involved in this process. (Wright et al, 2009, Bartlett et al, 2011 Mmp20 is expressed in secretory stage ameloblasts and also has effects on them maturation stage as well as on the mineralisation of mantle dentine. Klk4, present in both ameloblasts and odontoblasts, is expressed at the enamel transition and maturation phase.…”
Section: Amelogenesis and Developmental Defects Of Enamelmentioning
confidence: 99%
“…In the maturation phase Runx2 induces Klk4 and upregulates basal membrane protein expression to induce ameloblast attachment to the enamel matrix. (Brook, 2009, Wrightet al, 2009, Bartlett et al, 2011 In general, systemic factors that disturb the ameloblasts during the secretory stage cause restrictions of crystal elongation and result in pathologically thin, or hypoplastic enamel. On the other hand, disturbances during the transitional and/or maturation stage of amelogenesis result in pathologically soft (hypomaturated, hypomineralised) enamel of normal thicknesses.…”
Section: Amelogenesis and Developmental Defects Of Enamelmentioning
confidence: 99%
“…In addition to the role of processing enamel proteins, junctional complexes present on ameloblasts may also be cleaved by MMP20 to foster cell movement, which is necessary for the formation of the decussating enamel rod pattern. 10,11 Another proposed function of MMP20 is to activate KLK4. 12 …”
Section: Introductionmentioning
confidence: 99%